ARCHITECTURAL INGENUITY AND THE CONSTRUCTAL LAW: UNLEASHING MAXWELL'S DEMONS (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Architectural ingenuity is a concept that epitomizes the fusion of design aesthetics and scientific principles, yielding spatial configurations that marry visual allure with science, functional resilience, sustainability, and energetic efficiency. Within this paradigm, the arrow of time, as dictated by the second law of thermodynamics, assumes significance. The evolution of architectural ingenuity unveils an alternative temporal narrative, often overlooked in architectural theory. This narrative finds resonance with the constructal law, propounded by Adrian Bejan, where architectural ingenuity mirrors the dynamic flow systems' fundamental principles. It is a contemporary manifestation of Maxwell's demon, driving spatial design's refinement and evolution. This interplay between human creativity and natural laws sculpts artificial living environments – flow configurations, enhancing human experience while mirroring the universal tendency of flow systems to improve accessibility over time. Architectural ingenuity, fluid and evolving, shapes spaces in synchrony with the essence of time.
Keywords: Architectural ingenuity; Maxwell’s demons; Constructal law; Arrow of time; Living thermodynamics